2003
DOI: 10.1074/jbc.m209065200
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 Regulates Intracellular Trafficking and Cell Surface Delivery of β-Amyloid Precursor Protein

Abstract: Presenilins (PS1/PS2) play a critical role in proteolysis of ␤-amyloid precursor protein (␤APP) to generate ␤-amyloid, a peptide important in the pathogenesis of Alzheimer's disease. Nevertheless, several regulatory functions of PS1 have also been reported. Here we demonstrate, in neuroblastoma cells, that PS1 regulates the biogenesis of ␤APP-containing vesicles from the transGolgi network and the endoplasmic reticulum. PS1 deficiency or the expression of loss-of-function variants leads to robust vesicle forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 58 publications
7
128
1
Order By: Relevance
“…Indeed, Western blot analysis showed normal expression of AP3 subunits in PS-null melanocytes (data not shown). The fact that the APP C terminus does not have the dileucine motif and that PS was reported to affect APP trafficking to plasma membrane or endocytosis not known to mediate Tyr routing further corroborate with this notion (10,11). Further work is required to identify the mechanism where by PS regulates the trafficking of these diverse type I membrane proteins.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Indeed, Western blot analysis showed normal expression of AP3 subunits in PS-null melanocytes (data not shown). The fact that the APP C terminus does not have the dileucine motif and that PS was reported to affect APP trafficking to plasma membrane or endocytosis not known to mediate Tyr routing further corroborate with this notion (10,11). Further work is required to identify the mechanism where by PS regulates the trafficking of these diverse type I membrane proteins.…”
Section: Discussionmentioning
confidence: 51%
“…PS1 deficiency has been reported to result in aberrant trafficking and maturation of APP (10,11), Notch (12,13), tyrosine kinase receptor TrkB (14), ␤-and ␦-catenin (15,16), and nicastrin (17)(18)(19). Reports by Esselens et al (20) and Wilson et al (21) implicated a role of PS1 in the turnover of telencephalin and ␣-and ␤-synucleins, respectively.…”
Section: Ammalian Presenilins (Ps) Consists Of Two Homologous Pro-mentioning
confidence: 97%
“…Two of the most consistent cellular changes associated with both PS1 and PS2 FAD-associated mutations include ion channel dysfunction, such as defects in capacitative Ca 2ϩ entry (CCE) (16,17) and membrane trafficking defects, including diminished cell surface delivery of APP (15,(19)(20)(21). These A␤42-independent cellular changes may also contribute to the onset and/or neuropathological characteristics of presenilindependent FAD (22).…”
mentioning
confidence: 99%
“…Magnesium supplementation may be a safe and well--tolerated option for migraine prophylaxis in the prevention of paediatric migraine. However, while a double--blind placebo--controlled, randomized trial of patients aged 3 to 17 years found a statistically significant downward trend in headache frequency in those treated with magnesium oxide, the difference in the slopes of the two lines was not statistically significant (Wang et al, 2003). It could therefore not be determined if oral magnesium was superior to placebo in preventing frequent migraines in children and adolescents.…”
Section: Oral Magnesium Supplementationmentioning
confidence: 80%
“…Thus, delineation of how the intracellular trafficking of these secretases and APP are regulated is important for understanding AD pathogenesis. Although APP trafficking is regulated by multiple factors including PS1 (Cai et al, 2003), a major component of the γ--secretase complex, and phospholipase D1, a phospholipid--modifying enzyme, APP can reciprocally regulate PS1 trafficking. APP deficiency results in faster transport of PS1 from the trans--Golgi network to the cell surface and increased steady state levels of PS1 at the cell surface, which can be reversed by restoring APP levels (Liu et al, 2009 (Yu et al, 2010).…”
Section: Magnesium In Admentioning
confidence: 99%